A polishing liquid and preparation method thereof

By using a combination of micro powder material and water-based composite carrier liquid in the silicon carbide polishing liquid, the problems of low efficiency and abrasive chip accumulation in the existing silicon carbide polishing liquid are solved, and higher polishing quality and removal efficiency are achieved.

CN116144270BActive Publication Date: 2025-01-03CHONGQING SANAN SEMICONDUCTOR CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310139431.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-20
Publication Date
2025-01-03
Estimated Expiration
2043-02-20

AI Technical Summary

Technical Problem

The efficiency of existing silicon carbide polishing liquid is low, resulting in damage problems such as scratches, orange peels and micro-pits, and the accumulation of wear chips hinders the chemical effect of the polishing interface, reducing the removal efficiency.

Method used

Using a combination of micropowder and water-based composite carrier liquid, the micropowder includes abrasive particles and nanographite powder. Through scientific proportioning and step-by-step mixing methods, the lubricating performance and dispersion of the polishing liquid are improved, and the abrasive particles are agglomerated and enhanced. Protection of silicon carbide wafers.

Benefits of technology

It effectively reduces scratches and damage to silicon carbide wafers, improves polishing quality and removal efficiency, and ensures uniform dispersion and stability of the polishing liquid.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116144270B_ABST
    Figure CN116144270B_ABST
Patent Text Reader

Abstract

The present disclosure discloses a polishing liquid, which includes a micro-powder and a water-based composite carrier liquid, wherein the mass ratio of the micro-powder and the water-based composite carrier liquid is: the micro-powder is 2-40 parts, and the water-based composite carrier liquid is 60-98 parts; the micro-powder includes abrasive particles and nano-graphite powder. When the polishing liquid disclosed herein is used to polish an object to be polished, the lubrication performance of the interface between the object to be polished and the polishing pad is enhanced during the polishing process, the chip removal during the polishing process is accelerated, the abrasive particle agglomeration is effectively reduced, the scratches and other damages to the surface of the object to be polished are reduced, and the polishing quality is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure generally relates to the field of semiconductor technology, and more specifically, to a polishing liquid and a method for preparing the same. Background Art

[0002] Silicon carbide (SiC) is a new generation of semiconductor materials for manufacturing high-performance semiconductor devices such as ultra-high voltage power devices, deep ultraviolet optoelectronic devices, and high-brightness LEDs. After the single crystal growth of silicon carbide crystals is completed, they need to go through wafer manufacturing processes such as wafer cutting, ultra-precision grinding, CMP polishing (Chemical Mechanical Polishing) and cleaning to finally obtain a high-precision, ultra-smooth, and damage-free silicon carbide wafer substrate.

[0003] Silicon carbide has a Mohs hardness of up to 9.5 and is chemically inert. Traditional alkaline hydrogen peroxide-silicon oxide system polishing fluids are extremely inefficient for polishing silicon carbide and cannot meet the growing market demand. Therefore, the polishing fluid currently used in the industry is an acidic chemical mechanical polishing fluid that combines aluminum oxide with a strong oxidant, potassium permanganate. Since the hardness of aluminum oxide is much greater than that of silicon oxide, the scratches, orange peels, micro-pit defects, and other damages caused by the current mainstream acidic aluminum oxide polishing fluid products are greater than those caused by traditional alkaline silicon oxide polishing fluids.

[0004] In order to avoid serious scratches during the polishing process, the polishing liquid mainly relies on the use of nano-sized aluminum oxide or coated abrasives to improve the dispersion of abrasive particles in the polishing liquid. In the actual polishing process, nano-aluminum oxide is very easy to agglomerate to form large particles due to the influence of intermolecular forces, which introduces scratches and other damage to the silicon carbide wafer during the polishing process. On the other hand, as the polishing progresses, the increase in the accumulation of abrasive debris will aggravate the agglomeration of abrasive particles, further aggravating the scratches and other damage to the silicon carbide wafer. At the same time, the accumulation of abrasive debris also hinders the chemical action of the polishing interface and reduces the removal efficiency of the polishing material.

[0005] Therefore, it is urgent to develop a polishing solution that can improve the polishing quality. Summary of the invention

[0006] In order to at least solve one or more of the technical problems mentioned above, the present disclosure provides a polishing liquid and a preparation method thereof in multiple aspects.

[0007] In the first aspect, the present disclosure provides a polishing liquid, which includes a micropowder and a water-based composite carrier liquid, wherein the mass ratio of the micropowder and the water-based composite carrier liquid is: the micropowder is 2-40 parts, and the water-based composite carrier liquid is 60-98 parts; the micropowder includes abrasive particles and nano-graphite powder.

[0008] In some embodiments, the mass ratio of the abrasive particles in the micro-powder material is 20wt%-80wt%; the mass ratio of the nano-graphite powder in the micro-powder material is 20wt%-80wt%.

[0009] In some embodiments, the average particle size of the abrasive particles is 50 nm-5 μm, and the average particle size of the nano-graphite powder is 20 nm-500 nm.

[0010] In some embodiments, the water-based composite carrier liquid includes an oxidant, a surfactant, a suspending agent, a defoaming agent, a dispersing agent, a pH regulator and water, wherein the mass ratio of the components in the water-based composite carrier liquid is: water is 80-94 parts, the oxidant is 1-6 parts, the surfactant is 0.5-2 parts, the suspending agent is 0.1-0.5 parts, the defoaming agent is 0.1-0.3 parts, the dispersing agent is 0.5-4 parts, and the pH regulator is 0.05-0.3 parts.

[0011] In some embodiments, the oxidant includes one or more of potassium permanganate, sodium persulfate, potassium persulfate, sodium thiosulfate, sodium hypochlorite, potassium nitrate, chromic acid, perchromic acid and perchromic salts; and / or, the surfactant includes one or more of high molecular weight polymer polyvinyl pyrrolidone, sodium laurate, sodium oxalate, fatty alcohol and polyoxyethylene ether; and / or, the suspending agent includes one or more of bentonite and / or fumed silica; and / or, the defoaming agent includes one or more of propylene glycol, glycerol and mineral oil; and / or, the dispersant includes one or more of sodium nitrate, sodium oxalate, sodium hexametaphosphate, sodium pyrophosphate and sodium tripolyphosphate; and / or, the pH adjuster includes potassium hydroxide solution and / or nitric acid solution.

[0012] In some embodiments, the defoaming agent includes propylene glycol and glycerol, wherein the volume proportion of propylene glycol in the defoaming agent is 20%-30%, and the volume proportion of glycerol in the defoaming agent is 70%-80%.

[0013] In a second aspect, the present disclosure provides a method for preparing a polishing liquid, comprising: providing a micropowder material, wherein the micropowder material comprises abrasive particles and nano-graphite powder; providing a water-based composite carrier liquid; mixing 2-40 parts of the micropowder material with 60-98 parts of the water-based composite carrier liquid in a mass ratio to obtain a polishing liquid.

[0014] In some embodiments, the water-based composite carrier liquid includes: an oxidant, a surfactant, a suspending agent, a defoaming agent, a dispersing agent, a pH regulator and water, wherein the mass ratio of the components in the water-based composite carrier liquid is: 80-94 parts of water, 1-6 parts of the oxidant, 0.5-2 parts of the surfactant, 0.1-0.5 parts of the suspending agent, 0.1-0.3 parts of the defoaming agent, 0.5-4 parts of the dispersing agent, and 0.05-0.3 parts of the pH regulator.

[0015] In some embodiments, the step of mixing 2-40 parts of the micro-powder material with 60-98 parts of a water-based composite carrier liquid by mass to obtain a polishing liquid includes: mixing 1-6 parts of an oxidant by mass, 0.5-2 parts of a surfactant, 0.1-0.5 parts of a suspending agent, 0.5-4 parts of a dispersant and 80-94 parts of water to obtain a first water-based composite carrier liquid; mixing the first water-based composite carrier liquid with 0.1-0.3 parts by mass of a defoaming agent to obtain a second water-based composite carrier liquid; mixing the second water-based composite carrier liquid with the micro-powder material to obtain a first mixed liquid; adding a pH adjuster to the first mixed liquid to adjust the pH to 1-5 to obtain the polishing liquid.

[0016] In some embodiments, the mass ratio of the abrasive particles in the micro-powder material is 20wt%-80wt%; the mass ratio of the nano-graphite powder in the micro-powder material is 20wt%-80wt%.

[0017] The first aspect of the present disclosure provides a polishing liquid, which includes a micro-powder and a water-based composite carrier liquid, wherein the micro-powder includes abrasive particles and nano-graphite powder. When the polishing liquid of the present disclosure is used to polish an object to be polished, the lubrication performance of the interface between the object to be polished and the polishing pad is enhanced during the polishing process, and the chip removal during the polishing process is accelerated, thereby effectively reducing the abrasive particle agglomeration, reducing the damage such as scratches on the surface of the object to be polished, and improving the polishing quality.

[0018] The second aspect of the present disclosure provides a method for preparing a polishing liquid. The preparation method can obtain a polishing liquid with good lubrication performance and is beneficial to improving the polishing quality by mixing a micropowder material including nano-graphite powder with a water-based composite carrier liquid. Since the polishing liquid can be obtained by simply mixing the micropowder material with the water-based composite carrier liquid, the preparation method also has the characteristic of simple steps.

[0019] In some embodiments, the preparation method can be performed by first mixing an oxidant, a surfactant, a suspending agent, a dispersant and water to obtain a first water-based composite carrier liquid, then mixing the first water-based composite carrier liquid with a defoaming agent to obtain a second water-based composite carrier liquid, and then mixing the second water-based composite carrier liquid with a micropowder to obtain a first mixed liquid, and adding a pH adjuster to the first mixed liquid as a last step to obtain a polishing liquid. By adopting the method of step-by-step mixing of the micropowder and the water-based composite carrier liquid, the micropowder can be distributed more evenly in the polishing liquid. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] By reading the detailed description below with reference to the accompanying drawings, the above and other objects, features and advantages of the exemplary embodiments of the present disclosure will become readily understood. In the accompanying drawings, several embodiments of the present disclosure are shown in an exemplary and non-limiting manner, and the same or corresponding reference numerals represent the same or corresponding parts, wherein:

[0021] Figure 1 A flow chart showing a method for preparing a polishing liquid according to some embodiments of the present disclosure is shown;

[0022] Figure 2 A flow chart of a method for preparing a polishing liquid according to some other embodiments of the present disclosure is shown. DETAILED DESCRIPTION

[0023] The following will be combined with the drawings in the embodiments of the present disclosure to clearly and completely describe the technical solutions in the embodiments of the present disclosure. Obviously, the described embodiments are part of the embodiments of the present disclosure, not all of the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present disclosure.

[0024] It should be understood that the terms "include" and "comprising" used in the specification and claims of the present disclosure indicate the presence of described features, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or collections thereof.

[0025] It should also be understood that the terms used in this disclosure are only for the purpose of describing specific embodiments and are not intended to limit the disclosure. As used in this disclosure and claims, the singular forms of "a", "an", and "the" are intended to include the plural forms unless the context clearly indicates otherwise. It should also be further understood that the term "and / or" used in this disclosure and claims refers to any combination of one or more of the associated listed items and all possible combinations, including these combinations.

[0026] The specific implementation of the present disclosure is described in detail below with reference to the accompanying drawings.

[0027] The first aspect of the present disclosure provides a polishing liquid, which includes a micropowder and a water-based composite carrier liquid, wherein the mass ratio of the micropowder and the water-based composite carrier liquid is: the micropowder is 2-40 parts, wherein the micropowder includes abrasive particles and nano-graphite powder, and the water-based composite carrier liquid is 60-98 parts. The polishing liquid obtained by the present disclosure has good lubrication performance. When polishing the polished object, it can effectively reduce the agglomeration of abrasive particles, reduce the damage to the polished object such as scratches, orange peel, and pits, and improve the surface quality of the polished object. Preferably, the aforementioned polished object can be a semiconductor wafer, such as a silicon carbide wafer. It can be understood that the "part" in the mass ratio in the present disclosure refers to the basic unit of measurement representing the mass ratio relationship of multiple components. 1 part can represent any unit mass, such as 1g, 2g, 5g, 10g, 100g, etc., and can also be not limited to integer unit mass, for example, it can also represent 2.05g, etc. For another example, if the mass ratio of component A is a parts and the mass ratio of component B is b parts, it means that the ratio of the mass of component A to the mass of component B is a:b.

[0028] In some embodiments, the mass ratio of the aforementioned abrasive particles in the micro-powder can be 20wt%-80wt%, and the mass ratio of the nano-graphite powder in the micro-powder can be 20wt%-80wt%. The role of the abrasive particles in the polishing liquid is usually to use the higher hardness of the abrasive particles themselves to generate mechanical force on the surface of the object to be polished, and to remove the part of the surface of the object to be polished that needs to be removed, such as the passivation film, so as to achieve the purpose of flattening the surface of the object to be polished. In the actual polishing process, due to the intermolecular force, the abrasive particles are easy to agglomerate into large particles, and scratches and other damages are introduced to the polished object during the polishing process. Nano-graphite powder has excellent lubrication properties, and its regulation of the lubrication properties of the chemical mechanical polishing interface accelerates the chip removal of the polishing liquid during the polishing process, avoids the accumulation of a large amount of abrasive chips to hinder the chemical corrosion of the polishing liquid on the surface of the object to be polished, thereby improving the material removal rate. Furthermore, the present disclosure uses nano graphite powder with good lubrication performance and abrasive particles as micro powder materials. The addition of nano graphite powder increases the dispersion of the abrasive particles, reduces the agglomeration of the abrasive particles during the polishing process, and reduces the degree of scratches on the polished object.

[0029] In some other embodiments, the aforementioned abrasive particles may include one or more of silicon oxide, aluminum oxide, zirconium oxide, silicon carbide and diamond. Since the polished object, such as silicon carbide wafer, is usually covered with impurities such as oxides on its surface during the production process, in order to ensure that the silicon carbide wafer can maximize its function in the semiconductor device, the impurities need to be removed. When the polishing liquid is in the polishing process, the abrasive particles need to exert a mechanical effect on the impurities. For example, the abrasive particles can produce a cutting effect on the impurities such as oxides on the surface of the polished object to remove the impurities from the silicon carbide wafer. Therefore, the abrasive particles usually need to select materials with a certain hardness as abrasive particles, for example, the Mohs hardness of silicon oxide is 7, the Mohs hardness of aluminum oxide is 8.8, the Mohs hardness of zirconium oxide is 8.5, the Mohs hardness of silicon carbide is 9.5, and the Mohs hardness of diamond is 10. The above materials all have a high Mohs hardness and have the conditions of having a high hardness to become abrasive particles in the polishing liquid.

[0030] Furthermore, the particle size grade of the aforementioned abrasive is preferably D50, and the average particle size is 50nm-5μm; the particle size grade of the aforementioned nano-graphite powder is preferably D50, and the average particle size is 20nm-500nm. In general, when the abrasive size in the polishing liquid increases, the removal rate of the polished object increases, but at the same time, the scratches increase and the surface quality of the polished object decreases. If the size of the abrasive is too small, it is easy to agglomerate during the polishing process, increasing the scratches on the surface of the polished object. Therefore, the abrasive in the polishing liquid in the embodiment of the present disclosure is selected in the range of 50nm-5μm. In order to further improve the dispersion of the abrasive in the polishing liquid and increase the lubrication performance of the polishing liquid, the nano-graphite powder in the polishing liquid in the present disclosure is selected in the range of 20nm-500nm.

[0031] In other embodiments, the aforementioned water-based composite carrier liquid may include an oxidant, a surfactant, a suspending agent, a defoaming agent, a dispersant, a pH regulator and water. Among them, the oxidant is used to cause the polishing liquid to produce a chemical corrosion and dissolution effect on the surface of the object to be polished. The surfactant is a reagent for adjusting the surface activity of the polishing liquid. The surfactant can modify the surface of the micro-powder material, thereby adjusting the polishing efficiency of the polishing liquid, and at the same time help to remove materials such as the products of the polishing process, and avoid the residual substances on the surface after polishing. The influence on the consistency of the performance of the object to be polished. The suspending agent is used to make the polishing liquid have good suspension. If the micro-powder material settles during the polishing process, the polishing speed and polishing quality of the polishing liquid will be affected. The addition of a dispersant can interact with the particle surface of the micro-powder material, change the surface properties of the particles of the micro-powder material, and prevent the agglomeration of the micro-powder particles, so as to achieve a stable dispersion effect in the polishing liquid. The defoaming agent is used to eliminate the foam generated by the polishing liquid during the polishing process and inhibit the generation of more foam, and does not affect the polishing effect of the polishing liquid. pH adjusters are used to adjust the pH value of the polishing solution. The pH value has a significant impact on the etching of the surface of the polished object, the formation of oxide film, and the stability of the polishing solution. Therefore, the pH value of the polishing solution needs to be strictly controlled.

[0032] Preferably, the mass ratio of each component in the water-based composite carrier liquid can be: 80-94 parts of water, 1-6 parts of oxidant, 0.5-2 parts of surfactant, 0.1-0.5 parts of suspending agent, 0.1-0.3 parts of defoaming agent, 0.5-4 parts of dispersant, and 0.05-0.3 parts of pH regulator. The embodiment of the present disclosure is scientifically proportioned to make the mass ratio of each component in the water-based composite base preferably the above ratio, which can be any point value or a value between any two points. The water-based composite carrier liquid prepared according to the above ratio can enable the polishing liquid to exert the best polishing performance.

[0033] Further, in some embodiments, the oxidant may include one or more of potassium permanganate, sodium persulfate, potassium persulfate, sodium thiosulfate, sodium hypochlorite, potassium nitrate, chromic acid, perchromic acid and perchromic salts, etc.; and / or, the surfactant may include one or more of high molecular weight polymer polyvinyl pyrrolidone, sodium laurate, sodium oxalate, fatty alcohol and polyoxyethylene ether, etc.; and / or, the suspending agent may include one or more of bentonite and / or fumed silica, etc.; and / or, the defoamer may include one or more of propylene glycol, glycerol and mineral oil, etc.; and / or, the dispersant may include one or more of sodium nitrate, sodium oxalate, sodium hexametaphosphate, sodium pyrophosphate and sodium tripolyphosphate, etc.; and / or, the pH regulator may include potassium hydroxide solution and / or nitric acid solution. The defoamer may include propylene glycol and glycerol, etc., wherein the volume proportion of propylene glycol in the defoamer may be 20%-30%, and the volume proportion of glycerol in the defoamer may be 70%-80%. The components such as the defoaming agent shown in the embodiments of the present disclosure are exemplary and non-limiting. For example, those skilled in the art may select other common materials in the art that can reduce foam formation as the defoaming agent.

[0034] A second aspect of the present disclosure provides a method for preparing a polishing liquid. Figure 1 The following is a flow chart showing a method for preparing a polishing liquid according to some embodiments of the present disclosure. Figure 1 As shown, the preparation method 100 may include: in step S110, providing a micro powder material, wherein the micro powder material includes abrasive grains and nano graphite powder. The micro powder material plays a role in removing impurities on the surface of the polished object in the polishing liquid, and on the other hand, increases the lubricity between the polished object and the polishing disk, thereby ensuring the polishing quality and polishing efficiency of the polishing liquid. In some embodiments, the mass ratio of the aforementioned abrasive grains in the micro powder material is 20wt%-80wt%; the mass ratio of the nano graphite powder in the micro powder material is 20wt%-80wt%.

[0035] Next, at step S120, a water-based composite carrier liquid may be provided. The water-based composite carrier liquid provides a dispersible matrix for the micropowder in the polishing liquid, so that the micropowder can be evenly dispersed in the polishing liquid, and can also reduce the foam generated by the polishing liquid during the polishing process, maintain the stability of the micropowder in the polishing liquid, and so on. In some embodiments, in step S120, providing the water-based composite carrier liquid may include providing the water-based composite carrier liquid obtained by mixing the various components, or may include providing the various components of the water-based composite carrier liquid, so as to facilitate the subsequent step-by-step mixing and other processes when preparing the polishing liquid. In other embodiments, the mass ratio of the various components in the water-based composite carrier liquid may be: 80-94 parts of water, 1-6 parts of oxidant, 0.5-2 parts of surfactant, 0.1-0.5 parts of suspending agent, 0.1-0.3 parts of defoaming agent, 0.5-4 parts of dispersant, and 0.05-0.3 parts of pH regulator.

[0036] Next, in step S130, 2-40 parts of the micro powder material and 60-98 parts of the water-based composite carrier liquid are mixed to obtain a polishing liquid. The temperature of the above preparation process is preferably 20-30°C. It can be seen that the preparation process of the disclosed embodiment has low requirements for experimental conditions and mild experimental conditions.

[0037] Combination of the above Figure 1 The preparation method of the polishing liquid according to the embodiment of the present disclosure is exemplarily described. It can be understood that the above description is illustrative rather than restrictive.

[0038] Figure 2 The following is a flow chart of a method for obtaining a polishing liquid according to an embodiment of the present disclosure. Figure 2 The method 200 shown may be Figure 1 The step S130 shown in FIG. Figure 1 The description of step S130 may also be applied to the following description of method 200 .

[0039] like Figure 2 As shown, the method 200 may include: at step S231, an oxidant, a surfactant, a suspending agent, a dispersing agent and water may be mixed according to a preset mass ratio to obtain a first water-based composite base carrier liquid. In some embodiments, a mass ratio of 1-6 parts of an oxidant, 0.5-2 parts of a surfactant, 0.1-0.5 parts of a suspending agent, 0.5-4 parts of a dispersing agent and 80-94 parts of water may be mixed to obtain a first water-based composite base carrier liquid.

[0040] Next, at step S232, the first water-based composite carrier liquid is mixed with a defoaming agent having a mass fraction of 0.1-0.3 parts to obtain a second water-based composite carrier liquid. Then, the process can proceed to step S233, where the second water-based composite carrier liquid is mixed with the micropowder to obtain a first mixed liquid. Further, at step S234, a pH regulator is added to the first mixed liquid to adjust the pH to 1-5 to obtain a polishing liquid. The polishing liquid obtained in the embodiment of the present disclosure preferably has a pH of 1-5. In some embodiments, the pH regulator may be a potassium hydroxide solution and / or a nitric acid solution. For example, only a nitric acid solution may be used as a pH regulator to adjust the pH value of the first mixed liquid to 1-5. For example, in some application scenarios, before the pH regulator is added, the pH value of the first mixed liquid is less than 1, or the pH value of the first mixed liquid is less than the target value (e.g., pH=3), and a potassium hydroxide solution may be added to adjust the pH value so that the pH value of the first mixed liquid reaches 1-5 or more accurately reaches the target value. For another example, a nitric acid solution and a potassium hydroxide solution may be used to adjust the pH value of the first mixed solution to 1-5 or a target value. In some application scenarios, when the pH value of the first mixed solution is adjusted to exceed the range of 1-5 or the target value using a potassium hydroxide solution, a nitric acid solution may be used for back-drip adjustment.

[0041] The preparation method adopts a step-by-step mixing method of micro-powder and water-based composite carrier liquid, firstly, an oxidant, a surfactant, a suspending agent, a dispersant and water are mixed to obtain a first water-based composite carrier liquid, then the first water-based composite carrier liquid is mixed with a defoamer to obtain a second water-based composite carrier liquid, then the second water-based composite carrier liquid is mixed with micro-powder to obtain a first mixed liquid, and then a pH regulator is added to the first mixed liquid to obtain a polishing liquid. Compared with directly adding each component in the water-based composite carrier liquid to deionized water at the same time, the method disclosed in the present disclosure using a distributed mixing treatment can make the micro-powder more evenly distributed in the polishing liquid.

[0042] Combination of the above Figure 2 The method for preparing the polishing liquid according to the embodiment of the present disclosure is exemplarily described. Figure 2 The polishing liquid preparation method shown ensures the uniform dispersion of the micro-powder in the polishing liquid. The experimental process is simple and easy to operate, which is further beneficial to improving the polishing quality and polishing efficiency of the polishing liquid during the polishing process.

[0043] Example

[0044] In order to facilitate the understanding of the technical solution of the present disclosure, the following will be described in conjunction with specific embodiments. The following embodiments are provided here only for illustrative purposes of the present invention and should not be construed as specific limitations of the present disclosure. The chemical reagents used in the following embodiments are all commercially available analytically pure, and the experimental methods without specific conditions are usually carried out according to conventional experimental conditions or the recommendations of the manufacturer. The reagents or instruments without specifying the manufacturer or source are conventional products that can be purchased from the market.

[0045] Example 1

[0046] A polishing solution is prepared by the following steps:

[0047] Take 20.0 parts of α-alumina with an average particle size of 50 nm and 6.0 parts of nano-graphite powder with an average particle size of 50 nm, mix them in a three-dimensional mixer for 60 minutes to obtain a uniformly mixed powder, set the speed of the three-dimensional mixer to 10 r / min, and then pass the uniformly mixed powder through a 300-mesh sieve to obtain a micropowder for use.

[0048] Evenly sprinkle 3.8 parts of oxidant KMnO4, 0.5 parts of dispersant NaNO3, 2.0 parts of surfactant polyvinyl pyrrolidone K30 (hereinafter referred to as "K30"), and 0.5 parts of suspending agent bentonite into a stirring bucket containing 67.2 parts of deionized water, mix and stir evenly, set the stirring speed to 30 r / min, and shake on a shaker for 120 minutes after no obvious solid particles are visually observed, until all the solids are dissolved in water, to obtain the first water-based composite carrier liquid.

[0049] 0.2 parts of defoaming agent mineral oil was added to the first water-based composite base carrier liquid obtained above, and the mixture was mixed. The temperature was set at 25° C. in an ultrasonic cleaning machine, and ultrasonic dispersion was performed for 30 minutes to obtain a second water-based composite base carrier liquid.

[0050] The fine powder obtained above was mixed with the second water-based composite carrier liquid, placed in an ultrasonic stirring barrel and stirred for 60 minutes at room temperature, the ultrasonic frequency was set to 20KHz, and the stirring speed was set to 30r / min, and then placed in a ball mill for 60 minutes to grind and break up any large agglomerated particles, so that the fine powder was more evenly dispersed in the second water-based composite carrier liquid to obtain a first mixed liquid.

[0051] 0.3 parts of pH adjusting agent HNO3 was added dropwise to the first mixed solution obtained above to adjust the pH to 1-5 to obtain a polishing solution. The parts of each component of the polishing solution in this embodiment are all parts by mass.

[0052] Example 2

[0053] A polishing solution is prepared by the following steps:

[0054] Take 15.0 parts of α-alumina with an average particle size of 100nm and 6 parts of nano-graphite powder with an average particle size of 30nm, mix them for 60 minutes using a three-dimensional mixer to obtain a uniformly mixed powder, set the speed of the three-dimensional mixer to 50r / min, and then pass the uniformly mixed powder through a 300-mesh sieve to obtain a micropowder for use.

[0055] Evenly sprinkle 4.0 parts of oxidant KMnO4, 0.5 parts of dispersant sodium oxalate, 1.5 parts of surfactant K30, and 0.5 parts of suspending agent bentonite into a stirring bucket containing 72.0 parts of deionized water, mix and stir evenly, set the stirring speed to 200 r / min, and shake on a shaker for 120 minutes after no obvious solid particles are visually observed, until all the solids are dissolved in water, to obtain a first water-based composite carrier liquid.

[0056] 0.2 parts of defoaming agent mineral oil was added to the first water-based composite base carrier liquid obtained above, and the mixture was mixed. The temperature was set at 25° C. in an ultrasonic cleaning machine, and ultrasonic dispersion was performed for 60 minutes to obtain a second water-based composite base carrier liquid.

[0057] The fine powder obtained above was mixed with the second water-based composite carrier liquid, placed in an ultrasonic stirring barrel and stirred for 60 minutes at room temperature, the ultrasonic frequency was set to 20KHz, and the stirring speed was 50r / min, and then placed in a ball mill for 60 minutes to grind and break up any agglomerated large particles, so that the fine powder was more evenly dispersed in the second water-based composite carrier liquid to obtain a first mixed liquid.

[0058] 0.3 parts of pH adjusting agent HNO3 were added dropwise to the first mixed solution obtained above to adjust the pH to 1-5 to obtain a polishing solution. The parts of each component of the polishing solution in this embodiment are all parts by mass.

[0059] Example 3

[0060] A polishing solution is prepared by the following steps:

[0061] Take 5.0 parts of α-alumina with an average particle size of 200nm and 5.0 parts of nano-graphite powder with an average particle size of 100nm, mix them in a three-dimensional mixer for 60 minutes to obtain a uniformly mixed powder, set the speed of the three-dimensional mixer to 10r / min, and then pass the uniformly mixed powder through a 300-mesh sieve to obtain a micropowder for use.

[0062] Evenly sprinkle 5.3 parts of oxidant K2S2O8, 0.5 parts of dispersant sodium hexametaphosphate, 2.0 parts of surfactant K30, and 0.5 parts of suspending agent fumed silica into a stirring bucket containing 81.0 parts of deionized water, mix and stir evenly, set the stirring speed to 30 r / min, and shake on a shaker for 120 minutes after no obvious solid particles are visually observed, until all the solids are dissolved in water, to obtain a first water-based composite carrier liquid.

[0063] 0.2 parts of defoaming agent mineral oil was added to the first water-based composite base carrier liquid obtained above, and the mixture was mixed. The temperature was set at 25° C. in an ultrasonic cleaning machine, and ultrasonic dispersion was performed for 30 minutes to obtain a second water-based composite base carrier liquid.

[0064] The fine powder obtained above was mixed with the second water-based composite carrier liquid, placed in an ultrasonic stirring barrel and stirred for 60 minutes at room temperature, the ultrasonic frequency was set to 20KHz, and the stirring speed was set to 30r / min, and then placed in a ball mill for 60 minutes to grind and break up any large agglomerated particles, so that the fine powder was more evenly dispersed in the second water-based composite carrier liquid to obtain a first mixed liquid.

[0065] 0.3 parts of pH adjusting agent HNO3 were added dropwise to the first mixed solution obtained above to adjust the pH to 1-5 to obtain a polishing solution. The parts of each component of the polishing solution in this embodiment are all parts by mass.

[0066] Example 4

[0067] A polishing solution is prepared by the following steps:

[0068] Take 8.0 parts of α-alumina with an average particle size of 500nm and 6.0 parts of nano-graphite powder with an average particle size of 300nm, mix them in a three-dimensional mixer for 60 minutes to obtain a uniformly mixed powder, set the speed of the three-dimensional mixer to 10r / min, and then pass the uniformly mixed powder through a 300-mesh sieve to obtain a micropowder for use.

[0069] Evenly sprinkle 4.3 parts of oxidant KMnO4, 0.4 parts of dispersant sodium hexametaphosphate, 1.5 parts of surfactant polyoxyethylene ether, and 0.5 parts of suspending agent fumed silica into a stirring bucket containing 79.0 parts of deionized water, and stir evenly. Set the stirring speed to 30 r / min. After no obvious solid particles are visually observed, shake on a shaker for 120 minutes until all the solids are dissolved in water to obtain the first water-based composite carrier liquid.

[0070] 0.2 parts of defoaming agent mineral oil was added to the first water-based composite base carrier liquid obtained above, and the mixture was mixed. The temperature was set at 25° C. in an ultrasonic cleaning machine, and ultrasonic dispersion was performed for 30 minutes to obtain a second water-based composite base carrier liquid.

[0071] The fine powder obtained above was mixed with the second water-based composite carrier liquid, placed in an ultrasonic stirring barrel and stirred for 60 minutes at room temperature, the ultrasonic frequency was set to 20KHz, and the stirring speed was set to 30r / min, and then placed in a ball mill for 60 minutes to grind and break up any large agglomerated particles, so that the fine powder was more evenly dispersed in the second water-based composite carrier liquid to obtain a first mixed liquid.

[0072] 0.3 parts of pH adjusting agent HNO3 was added dropwise to the first mixed solution obtained above to adjust the pH to 1-5 to obtain a polishing solution. The parts of each component of the polishing solution in this embodiment are all parts by mass.

[0073] Example 5

[0074] A polishing solution is prepared by the following steps:

[0075] Take 10 parts of α-alumina with an average particle size of 1000nm and 8.0 parts of nano-graphite powder with an average particle size of 500nm, mix them in a three-dimensional mixer for 60 minutes to obtain a uniformly mixed powder, set the speed of the three-dimensional mixer to 10r / min, and then pass the uniformly mixed powder through a 300-mesh sieve to obtain a micropowder for use.

[0076] Evenly sprinkle 5.0 parts of oxidant K2S2O8, 0.5 parts of dispersant NaNO3, 2.0 parts of surfactant K30, and 0.5 parts of suspending agent bentonite into a stirring bucket containing 73.4 parts of deionized water, mix and stir evenly, set the stirring speed to 30 r / min, and shake on a shaker for 120 minutes after no obvious solid particles are visually observed, until all the solids are dissolved in water, to obtain a first water-based composite carrier liquid.

[0077] 0.3 parts of defoaming agent mineral oil was added to the first water-based composite base carrier liquid obtained above, and the mixture was mixed. The temperature was set at 25° C. in an ultrasonic cleaning machine, and ultrasonic dispersion was performed for 30 minutes to obtain a second water-based composite base carrier liquid.

[0078] The fine powder obtained above was mixed with the second water-based composite carrier liquid, placed in an ultrasonic stirring barrel and stirred for 60 minutes at room temperature, the ultrasonic frequency was set to 20KHz, and the stirring speed was set to 30r / min, and then placed in a ball mill for 60 minutes to grind and break up any large agglomerated particles, so that the fine powder was more evenly dispersed in the second water-based composite carrier liquid to obtain a first mixed liquid.

[0079] 0.3 parts of pH adjusting agent HNO3 was added dropwise to the first mixed solution obtained above to adjust the pH to 1-5 to obtain a polishing solution. The parts of each component of the polishing solution in this embodiment are all parts by mass.

[0080] Example 6

[0081] A polishing solution is prepared by the following steps:

[0082] Take 20.0 parts of silicon oxide with an average particle size of 100 nm and 20.0 parts of nano-graphite powder with an average particle size of 20 nm, mix them in a three-dimensional mixer for 60 minutes to obtain a uniformly mixed powder, set the speed of the three-dimensional mixer to 10 r / min, and then pass the uniformly mixed powder through a 300-mesh sieve to obtain a micropowder for use.

[0083] Sprinkle 6 parts of oxidant sodium persulfate, 4 parts of dispersant sodium pyrophosphate, 0.5 parts of surfactant sodium laurate, and 0.1 parts of suspending agent bentonite evenly into a stirring bucket containing 94 parts of deionized water, and stir evenly. Set the stirring speed to 30 r / min. After no obvious solid particles are visually observed, shake on a shaker for 120 minutes until all the solids are dissolved in water to obtain a first water-based composite carrier liquid.

[0084] Add 0.3 parts of a mixture of propylene glycol and glycerol, a defoaming agent, to the first water-based composite carrier liquid obtained above, wherein the volume proportion of propylene glycol in the defoaming agent is 20%, and the volume proportion of glycerol in the defoaming agent is 80%. Set the temperature to 25° C. in an ultrasonic cleaning machine, and perform ultrasonic dispersion for 30 minutes to obtain a second water-based composite carrier liquid.

[0085] The fine powder obtained above was mixed with the second water-based composite carrier liquid, placed in an ultrasonic stirring barrel and stirred for 60 minutes at room temperature, the ultrasonic frequency was set to 20KHz, and the stirring speed was set to 30r / min, and then placed in a ball mill for 60 minutes to grind and break up any large agglomerated particles, so that the fine powder was more evenly dispersed in the second water-based composite carrier liquid to obtain a first mixed liquid.

[0086] 0.25 parts of pH adjusting agent HNO3 and 0.05 parts of potassium hydroxide solution were added dropwise to the first mixed solution obtained above to adjust the pH to 1-5 to obtain a polishing solution. The parts of each component of the polishing solution in this embodiment are all parts by mass.

[0087] Example 7

[0088] A polishing solution is prepared by the following steps:

[0089] Take 5.0 parts of α-alumina with an average particle size of 50nm and 20.0 parts of nano-graphite powder with an average particle size of 50nm, mix them in a three-dimensional mixer for 60 minutes to obtain a uniformly mixed powder, set the speed of the three-dimensional mixer to 10r / min, and then pass the uniformly mixed powder through a 300-mesh sieve to obtain a micropowder for use.

[0090] Evenly sprinkle 3.8 parts of oxidant KMnO4, 0.5 parts of dispersant sodium tripolyphosphate, 2.0 parts of surfactant polyvinyl pyrrolidone, and 0.5 parts of suspending agent bentonite into a stirring bucket containing 67.2 parts of deionized water, and stir evenly. Set the stirring speed to 30 r / min. After no obvious solid particles are visually observed, shake on a shaker for 120 minutes until all the solids are dissolved in water to obtain the first water-based composite carrier liquid.

[0091] Add 0.1 part of a mixture of propylene glycol and glycerol, a defoaming agent, to the first water-based composite carrier liquid obtained above, wherein the volume proportion of propylene glycol in the defoaming agent is 30%, and the volume proportion of glycerol in the defoaming agent is 70%. Set the temperature to 25° C. in an ultrasonic cleaning machine, and perform ultrasonic dispersion for 30 minutes to obtain a second water-based composite carrier liquid.

[0092] The fine powder obtained above was mixed with the second water-based composite carrier liquid, placed in an ultrasonic stirring barrel and stirred for 60 minutes at room temperature, the ultrasonic frequency was set to 20KHz, and the stirring speed was set to 30r / min, and then placed in a ball mill for 60 minutes to grind and break up any large agglomerated particles, so that the fine powder was more evenly dispersed in the second water-based composite carrier liquid to obtain a first mixed liquid.

[0093] 0.3 parts of pH adjusting agent HNO3 was added dropwise to the first mixed solution obtained above to adjust the pH to 1-5 to obtain a polishing solution. The parts of each component of the polishing solution in this embodiment are all parts by mass.

[0094] Example 8

[0095] A polishing solution is prepared by the following steps:

[0096] Take 32.0 parts of zirconium oxide with an average particle size of 5 μm and 8.0 parts of nano-graphite powder with an average particle size of 500 nm, mix them in a three-dimensional mixer for 60 minutes to obtain a uniformly mixed powder, set the speed of the three-dimensional mixer to 10 r / min, and then pass the uniformly mixed powder through a 300-mesh sieve to obtain a micropowder for use.

[0097] 1.0 part of oxidant sodium thiosulfate, 0.5 part of dispersant sodium tripolyphosphate, 2.0 parts of surfactant fatty alcohol, and 0.5 part of suspending agent bentonite and fumed silica mixture (mass ratio 1:1) are evenly sprinkled into a stirring bucket containing 80 parts of deionized water and mixed and stirred evenly. The stirring speed is set to 30 r / min. After no obvious solid particles are visually observed, shake on a shaker for 120 minutes until all the solids are dissolved in water to obtain a first water-based composite carrier liquid.

[0098] 0.2 parts of defoaming agent mineral oil was added to the first water-based composite base carrier liquid obtained above, and the mixture was mixed. The temperature was set at 25° C. in an ultrasonic cleaning machine, and ultrasonic dispersion was performed for 30 minutes to obtain a second water-based composite base carrier liquid.

[0099] The fine powder obtained above was mixed with the second water-based composite carrier liquid, placed in an ultrasonic stirring barrel and stirred for 60 minutes at room temperature, the ultrasonic frequency was set to 20KHz, and the stirring speed was set to 30r / min, and then placed in a ball mill for 60 minutes to grind and break up any large agglomerated particles, so that the fine powder was more evenly dispersed in the second water-based composite carrier liquid to obtain a first mixed liquid.

[0100] 0.2 parts of pH adjusting agent HNO3 were added dropwise to the first mixed solution obtained above to adjust the pH to 1-5 to obtain a polishing solution. The parts of each component of the polishing solution in this embodiment are all parts by mass.

[0101] Example 9

[0102] A polishing solution is prepared by the following steps:

[0103] Take 20.0 parts of silicon carbide with an average particle size of 50 nm and 6.0 parts of nano-graphite powder with an average particle size of 50 nm, mix them in a three-dimensional mixer for 60 minutes to obtain a uniformly mixed powder, set the speed of the three-dimensional mixer to 10 r / min, and then pass the uniformly mixed powder through a 300-mesh sieve to obtain a micropowder for use.

[0104] 3.8 parts of oxidant sodium hypochlorite, 0.5 parts of dispersant NaNO3, 2.0 parts of a mixture of surfactant sodium oxalate and sodium laurate (mass ratio is 1:1), and 0.5 parts of suspending agent bentonite are evenly sprinkled into a stirring bucket containing 67.2 parts of deionized water, and mixed and stirred evenly. The stirring speed is set to 30 r / min. After no obvious solid particles are visually observed, shake on a shaker for 120 minutes until all the solids are dissolved in water to obtain a first water-based composite carrier liquid.

[0105] 0.2 parts of defoaming agent mineral oil was added to the first water-based composite base carrier liquid obtained above, and the mixture was mixed. The temperature was set at 25° C. in an ultrasonic cleaning machine, and ultrasonic dispersion was performed for 30 minutes to obtain a second water-based composite base carrier liquid.

[0106] The fine powder obtained above was mixed with the second water-based composite carrier liquid, placed in an ultrasonic stirring barrel and stirred for 60 minutes at room temperature, the ultrasonic frequency was set to 20KHz, and the stirring speed was set to 30r / min, and then placed in a ball mill for 60 minutes to grind and break up any large agglomerated particles, so that the fine powder was more evenly dispersed in the second water-based composite carrier liquid to obtain a first mixed liquid.

[0107] 0.3 parts of pH adjusting agent HNO3 were added dropwise to the first mixed solution obtained above to adjust the pH to 1-5 to obtain a polishing solution. The parts of each component of the polishing solution in this embodiment are all parts by mass.

[0108] Example 10

[0109] A polishing solution is prepared by the following steps:

[0110] Take 6.0 parts of diamond with an average particle size of 50nm and 24.0 parts of nano-graphite powder with an average particle size of 100nm, mix them in a three-dimensional mixer for 60 minutes to obtain a uniformly mixed powder, set the speed of the three-dimensional mixer to 10r / min, and then pass the uniformly mixed powder through a 300-mesh sieve to obtain a micropowder for use.

[0111] 3.8 parts of oxidant potassium nitrate, 0.5 parts of a mixture of dispersants NaNO3 and sodium oxalate (mass ratio 1:1), 2.0 parts of surfactant K30, and 0.5 parts of suspending agent bentonite are evenly sprinkled into a stirring bucket containing 67.2 parts of deionized water, and mixed and stirred evenly. The stirring speed is set to 30 r / min. After no obvious solid particles are visually observed, shake on a shaker for 120 minutes until all the solids are dissolved in water to obtain a first water-based composite carrier liquid.

[0112] 0.2 parts of defoaming agent mineral oil was added to the first water-based composite base carrier liquid obtained above, and the mixture was mixed. The temperature was set at 25° C. in an ultrasonic cleaning machine, and ultrasonic dispersion was performed for 30 minutes to obtain a second water-based composite base carrier liquid.

[0113] The fine powder obtained above was mixed with the second water-based composite carrier liquid, placed in an ultrasonic stirring barrel and stirred for 60 minutes at room temperature, the ultrasonic frequency was set to 20KHz, and the stirring speed was set to 30r / min, and then placed in a ball mill for 60 minutes to grind and break up any large agglomerated particles, so that the fine powder was more evenly dispersed in the second water-based composite carrier liquid to obtain a first mixed liquid.

[0114] 0.3 parts of pH adjusting agent HNO3 was added dropwise to the first mixed solution obtained above to adjust the pH to 1-5 to obtain a polishing solution. The parts of each component of the polishing solution in this embodiment are all parts by mass.

[0115] Embodiment 11

[0116] A polishing solution is prepared by the following steps:

[0117] Take 24.0 parts of a mixture of α-alumina and silicon oxide (mass ratio 1:1) with an average particle size of 100 nm and 6.0 parts of nano-graphite powder with an average particle size of 50 nm, mix them for 60 minutes using a three-dimensional mixer to obtain a uniformly mixed powder, set the speed of the three-dimensional mixer to 10 r / min, and then pass the uniformly mixed powder through a 300-mesh sieve to obtain a micropowder for use.

[0118] 3.8 parts of a mixture of oxidizing agent perchromic acid and perchromic salt (mass ratio 1:1), 0.5 parts of dispersant NaNO3, 2.0 parts of surfactant K30, and 0.5 parts of suspending agent bentonite are evenly sprinkled into a stirring bucket containing 67.2 parts of deionized water, and mixed and stirred evenly. The stirring speed is set to 30 r / min. After no obvious solid particles are visually observed, shake on a shaker for 120 minutes until all the solids are dissolved in water to obtain a first water-based composite carrier liquid.

[0119] 0.2 parts of defoaming agent mineral oil was added to the first water-based composite base carrier liquid obtained above, and the mixture was mixed. The temperature was set at 25° C. in an ultrasonic cleaning machine, and ultrasonic dispersion was performed for 30 minutes to obtain a second water-based composite base carrier liquid.

[0120] The fine powder obtained above was mixed with the second water-based composite carrier liquid, placed in an ultrasonic stirring barrel and stirred for 60 minutes at room temperature, the ultrasonic frequency was set to 20KHz, and the stirring speed was set to 30r / min, and then placed in a ball mill for 60 minutes to grind and break up any large agglomerated particles, so that the fine powder was more evenly dispersed in the second water-based composite carrier liquid to obtain a first mixed liquid.

[0121] 0.1 part of pH adjusting agent HNO3 was added dropwise to the first mixed solution obtained above to adjust the pH to 1-5 to obtain a polishing solution. The parts of each component of the polishing solution in this embodiment are all parts by mass.

[0122] Example 12

[0123] A polishing solution is prepared by the following steps:

[0124] Take 1.0 part of α-alumina with an average particle size of 50nm and 1.0 part of nano-graphite powder with an average particle size of 50nm, mix them in a three-dimensional mixer for 60 minutes to obtain a uniformly mixed powder, set the speed of the three-dimensional mixer to 10r / min, and then pass the uniformly mixed powder through a 300-mesh sieve to obtain a micropowder for use.

[0125] Evenly sprinkle 1.0 part of chromic acid, an oxidizing agent, 0.5 part of NaNO3, a dispersant, 2.0 parts of K30, and a suspending agent, 0.5 part of bentonite, into a stirring bucket containing 91.85 parts of deionized water, and stir them evenly. Set the stirring speed to 30 r / min. After no obvious solid particles are visually observed, shake on a shaker for 120 minutes until all the solids are dissolved in water to obtain a first water-based composite carrier liquid.

[0126] 0.1 parts of defoaming agent mineral oil was added to the first water-based composite base carrier liquid obtained above, and the mixture was mixed. The temperature was set at 25° C. in an ultrasonic cleaning machine, and ultrasonic dispersion was performed for 30 minutes to obtain a second water-based composite base carrier liquid.

[0127] The fine powder obtained above was mixed with the second water-based composite carrier liquid, placed in an ultrasonic stirring barrel and stirred for 60 minutes at room temperature, the ultrasonic frequency was set to 20KHz, and the stirring speed was set to 30r / min, and then placed in a ball mill for 60 minutes to grind and break up any large agglomerated particles, so that the fine powder was more evenly dispersed in the second water-based composite carrier liquid to obtain a first mixed liquid.

[0128] 0.05 parts of pH adjusting agent HNO3 were added dropwise to the first mixed solution obtained above to adjust the pH to 1-5 to obtain a polishing solution. The parts of each component of the polishing solution in this embodiment are all parts by mass.

[0129] In order to explain the polishing effect of the polishing liquid obtained in the disclosed embodiment, the inventors also took the above-mentioned embodiments 1-5 as examples and conducted comparative experiments respectively. The experimental process of the comparative examples will be specifically described below.

[0130] Comparative Example 1

[0131] A polishing solution is prepared by the following steps:

[0132] Take 20.0 parts of α-alumina with an average particle size of 50 nm and pass it through a 300-mesh sieve to obtain a fine powder for use.

[0133] Evenly sprinkle 4.0 parts of oxidant KMnO4, 0.5 parts of dispersant NaNO3, 2.0 parts of surfactant K30, and 0.5 parts of suspending agent bentonite into a stirring bucket containing 73.0 parts of deionized water, mix and stir evenly, set the stirring speed to 30 r / min, and shake on a shaker for 120 minutes after no obvious solid particles are visually observed, until all the solids are dissolved in water, to obtain a first water-based composite carrier liquid.

[0134] 0.3 parts of defoaming agent mineral oil was added to the first water-based composite base carrier liquid obtained above, and the mixture was mixed. The temperature was set at 25° C. in an ultrasonic cleaning machine, and ultrasonic dispersion was performed for 30 minutes to obtain a second water-based composite base carrier liquid.

[0135] The fine powder obtained above was mixed with the second water-based composite carrier liquid, placed in an ultrasonic stirring barrel and stirred for 60 minutes at room temperature, the ultrasonic frequency was set to 20KHz, and the stirring speed was set to 30r / min, and then placed in a ball mill for 60 minutes to grind and break up any large agglomerated particles, so that the fine powder was more evenly dispersed in the second water-based composite carrier liquid to obtain a first mixed liquid.

[0136] 0.3 parts of pH adjusting agent HNO3 was added dropwise to the first mixed solution obtained above to adjust the pH to 1-5 to obtain a polishing solution. The parts of each component of the polishing solution in this embodiment are all parts by mass.

[0137] Comparative Example 2

[0138] A polishing solution is prepared by the following steps:

[0139] Take 15.0 parts of α-alumina with an average particle size of 100 nm and pass it through a 300-mesh sieve to obtain a fine powder for use.

[0140] Evenly sprinkle 4.3 parts of oxidant KMnO4, 0.5 parts of dispersant sodium oxalate, 2.0 parts of surfactant K30, and 0.5 parts of suspending agent bentonite into a stirring bucket containing 77.2 parts of deionized water, mix and stir evenly, set the stirring speed to 200 r / min, and shake on a shaker for 120 minutes after no obvious solid particles are visually observed, until all the solids are dissolved in water, to obtain a first water-based composite carrier liquid.

[0141] 0.2 parts of defoaming agent mineral oil was added to the first water-based composite base carrier liquid obtained above, and the mixture was mixed. The temperature was set at 25° C. in an ultrasonic cleaning machine, and ultrasonic dispersion was performed for 60 minutes to obtain a second water-based composite base carrier liquid.

[0142] The fine powder obtained above was mixed with the second water-based composite carrier liquid, placed in an ultrasonic stirring barrel and stirred for 60 minutes at room temperature, the ultrasonic frequency was set to 20KHz, and the stirring speed was 50r / min, and then placed in a ball mill for 60 minutes to grind and break up any agglomerated large particles, so that the fine powder was more evenly dispersed in the second water-based composite carrier liquid to obtain a first mixed liquid.

[0143] 0.3 parts of pH adjusting agent HNO3 were added dropwise to the first mixed solution obtained above to adjust the pH to 1-5 to obtain a polishing solution. The parts of each component of the polishing solution in this embodiment are all parts by mass.

[0144] Comparative Example 3

[0145] A polishing solution is prepared by the following steps:

[0146] Take 5.0 parts of α-alumina with an average particle size of 200 nm and pass it through a 300-mesh sieve to obtain a fine powder for use.

[0147] Evenly sprinkle 6.0 parts of oxidant K2S2O8, 0.5 parts of dispersant sodium hexametaphosphate, 2.0 parts of surfactant K30, and 0.5 parts of suspending agent fumed silica into a stirring bucket containing 85.3 parts of deionized water, and stir evenly. Set the stirring speed to 30 r / min. After no obvious solid particles are visually observed, shake on a shaker for 120 minutes until all the solids are dissolved in water to obtain a first water-based composite carrier liquid.

[0148] 0.3 parts of defoaming agent mineral oil was added to the first water-based composite base carrier liquid obtained above, and the mixture was mixed. The temperature was set at 25° C. in an ultrasonic cleaning machine, and ultrasonic dispersion was performed for 30 minutes to obtain a second water-based composite base carrier liquid.

[0149] The fine powder obtained above was mixed with the second water-based composite carrier liquid, placed in an ultrasonic stirring barrel and stirred for 60 minutes at room temperature, the ultrasonic frequency was set to 20KHz, and the stirring speed was set to 30r / min, and then placed in a ball mill for 60 minutes to grind and break up any large agglomerated particles, so that the fine powder was more evenly dispersed in the second water-based composite carrier liquid to obtain a first mixed liquid.

[0150] 0.4 parts of pH adjusting agent HNO3 were added dropwise to the first mixed solution obtained above to adjust the pH to 1-5 to obtain a polishing solution. The parts of each component of the polishing solution in this embodiment are all parts by mass.

[0151] Comparative Example 4

[0152] Take 8.0 parts of α-alumina with an average particle size of 500 nm and pass it through a 300-mesh sieve to obtain a fine powder for use.

[0153] Evenly sprinkle 4.6 parts of oxidant KMnO4, 0.4 parts of dispersant sodium hexametaphosphate, 1.5 parts of surfactant polyoxyethylene ether, and 0.5 parts of suspending agent fumed silica into a stirring bucket containing 84.5 parts of deionized water, and stir evenly. Set the stirring speed to 30 r / min. After no obvious solid particles are visually observed, shake on a shaker for 120 minutes until all the solids are dissolved in water to obtain the first water-based composite carrier liquid.

[0154] 0.2 parts of defoaming agent mineral oil was added to the first water-based composite base carrier liquid obtained above, and the mixture was mixed. The temperature was set at 25° C. in an ultrasonic cleaning machine, and ultrasonic dispersion was performed for 30 minutes to obtain a second water-based composite base carrier liquid.

[0155] The fine powder obtained above was mixed with the second water-based composite carrier liquid, placed in an ultrasonic stirring barrel and stirred for 60 minutes at room temperature, the ultrasonic frequency was set to 20KHz, and the stirring speed was set to 30r / min, and then placed in a ball mill for 60 minutes to grind and break up any large agglomerated particles, so that the fine powder was more evenly dispersed in the second water-based composite carrier liquid to obtain a first mixed liquid.

[0156] 0.3 parts of pH adjusting agent HNO3 were added dropwise to the first mixed solution obtained above to adjust the pH to 1-5 to obtain a polishing solution. The parts of each component of the polishing solution in this embodiment are all parts by mass.

[0157] Comparative Example 5

[0158] A polishing solution is prepared by the following steps:

[0159] Take 10 parts of α-alumina with an average particle size of 1000 nm and pass it through a 300-mesh sieve to obtain a fine powder for use.

[0160] Evenly sprinkle 5.4 parts of oxidant K2S2O8, 0.5 parts of dispersant NaNO3, 2.0 parts of surfactant K30, and 0.5 parts of suspending agent bentonite into a stirring bucket containing 81.0 parts of deionized water, mix and stir evenly, set the stirring speed to 30 r / min, and shake on a shaker for 120 minutes after no obvious solid particles are visually observed, until all the solids are dissolved in water, to obtain a first water-based composite carrier liquid.

[0161] 0.3 parts of defoaming agent mineral oil was added to the first water-based composite base carrier liquid obtained above, and the mixture was mixed. The temperature was set at 25° C. in an ultrasonic cleaning machine, and ultrasonic dispersion was performed for 30 minutes to obtain a second water-based composite base carrier liquid.

[0162] The fine powder obtained above was mixed with the second water-based composite carrier liquid, placed in an ultrasonic stirring barrel and stirred for 60 minutes at room temperature, the ultrasonic frequency was set to 20KHz, and the stirring speed was set to 30r / min, and then placed in a ball mill for 60 minutes to grind and break up any large agglomerated particles, so that the fine powder was more evenly dispersed in the second water-based composite carrier liquid to obtain a first mixed liquid.

[0163] 0.3 parts of pH adjusting agent HNO3 was added dropwise to the first mixed solution obtained above to adjust the pH to 1-5 to obtain a polishing solution. The parts of each component of the polishing solution in this embodiment are all parts by mass.

[0164] Based on the above description, the present disclosure conducted 17 experimental treatments, which are divided into Examples 1 to 12 and Comparative Examples 1 to 5, and the temperature of the above experimental process is preferably 20-30° C. For convenient and intuitive comparison and description, the components and addition ratios in Examples 1-5 and Comparative Examples 1-5 are shown in the form of tables below, as shown in Tables 1 and 2.

[0165] Table 1

[0166]

[0167] Table 2

[0168]

[0169] Further, in order to verify the polishing effect of the polishing liquid obtained by the disclosed embodiment, the inventors conducted subsequent test experiments on the polishing liquid obtained by the above embodiments 1-5 and comparative examples 1-5. Specifically, the polishing liquid prepared by the above embodiments 1 to 5 and comparative examples 1 to 5 was used to polish the silicon carbide wafer. The processing machine used in the polishing process is a polishing machine, and the processing parameters of the polishing process are set as follows: polishing head pressure 60kg, polishing disc speed 30r / min, polishing head speed 50r / min, polishing liquid flow 240r / min, polishing time 120min, and the workpiece processed in the polishing process is a 6-inch silicon carbide wafer. After polishing, the silicon carbide wafer is cleaned and dried, and the mass of the silicon carbide wafer before and after polishing is weighed using an analytical balance, and the material removal rate is calculated based on the difference in silicon carbide mass before and after polishing. The scratch detection machine is used to detect the scratch condition of the silicon carbide wafer after polishing, and the total length of the scratch is counted. In addition, the surface roughness of the silicon carbide wafer after polishing is measured using an AFM atomic force microscope. The experimental results are shown in Table 3.

[0170] Table 3

[0171]

[0172] As shown in Table 3, when the polishing liquid obtained in Examples 1 to 5 of the present disclosure is used to polish the silicon carbide wafer, the material removal rate is between 2.47-3.17 μm / h, the surface roughness is between 0.125-0.233 nm, and the total length of the scratch is between 12-84 mm. Compared with the polishing liquid obtained in Comparative Examples 1 to 5, the components in the polishing liquid obtained in Examples 1 to 5 of the present disclosure play a synergistic role, and the polishing liquid has excellent lubrication performance. When polishing the silicon carbide wafer, it can accelerate the chip removal during the polishing process, protect the suspension dispersion system of the polishing liquid from being destroyed by the accumulated abrasive chips during the polishing process, reduce the agglomeration of abrasive particles and abrasive chips to form large particles, and further reduce the scratches on the surface of the silicon carbide wafer caused by this. The polishing liquid of the present disclosure embodiment can also reduce the agglomeration of the abrasive particles themselves, reduce the damage such as scratches on the silicon carbide wafer, and improve the surface quality and polishing material removal rate of the silicon carbide wafer after polishing.

[0173] Although multiple embodiments of the present disclosure have been shown and described herein, it will be apparent to those skilled in the art that such embodiments are provided by way of example only. Those skilled in the art may think of many changes, modifications, and alternatives without departing from the thought and spirit of the present disclosure. It should be understood that in the process of practicing the present disclosure, various alternatives to the embodiments of the present disclosure described herein may be adopted. The attached claims are intended to define the scope of protection of the present disclosure, and therefore cover equivalents or alternatives within the scope of these claims.

Claims

1. A polishing liquid, characterized in that: It comprises a micro powder material and a water-based composite carrier liquid, wherein the mass ratio of the micro powder material to the water-based composite carrier liquid is: The micro powder material is 2-40 parts, and the water-based composite base carrier liquid is 60-98 parts; The water-based composite carrier liquid includes an oxidant, a surfactant, a suspending agent, a defoaming agent, a dispersing agent, a pH regulator and water; wherein the defoaming agent is used to eliminate the foam generated by the polishing liquid during the polishing process and inhibit the generation of more foam, and the pH regulator is used to adjust the pH of the polishing liquid to 1-5; The defoaming agent includes one or more of propylene glycol, glycerol and mineral oil; The micro powder material includes abrasive particles and nano graphite powder; The average particle size of the abrasive grains is 50nm-5μm, and the average particle size of the nano graphite powder is 20nm-500nm.

2. The polishing liquid according to claim 1, characterized in that The mass proportion of the abrasive particles in the micro powder is 20wt%-80wt%; The mass proportion of the nano graphite powder in the micro powder material is 20wt%-80wt%.

3. The polishing liquid according to claim 1, characterized in that The abrasive grains include one or more of silicon oxide, aluminum oxide, zirconium oxide, silicon carbide and diamond.

4. The polishing liquid according to claim 1, characterized in that The mass ratio of each component in the water-based composite carrier liquid is: The water is 80-94 parts, the oxidant is 1-6 parts, the surfactant is 0.5-2 parts, the suspending agent is 0.1-0.5 parts, the defoaming agent is 0.1-0.3 parts, the dispersant is 0.5-4 parts, and the pH regulator is 0.05-0.3 parts.

5. The polishing liquid according to claim 4, characterized in that The oxidant comprises one or more of potassium permanganate, sodium persulfate, potassium persulfate, sodium thiosulfate, sodium hypochlorite, potassium nitrate, chromic acid, perchromic acid and perchromic salt; and / or, The surfactant includes one or more of high molecular weight polymer polyvinyl pyrrolidone, sodium laurate, sodium oxalate, fatty alcohol and polyoxyethylene ether; and / or, The suspending agent comprises one or more of bentonite and / or fumed silica; and / or, The dispersant comprises one or more of sodium nitrate, sodium oxalate, sodium hexametaphosphate, sodium pyrophosphate and sodium tripolyphosphate; and / or, The pH adjuster includes potassium hydroxide solution and / or nitric acid solution.

6. The polishing liquid according to claim 1, characterized in that The defoaming agent comprises propylene glycol and glycerol, wherein the volume proportion of propylene glycol in the defoaming agent is 20%-30%, and the volume proportion of glycerol in the defoaming agent is 70%-80%.

7. A method for preparing a polishing liquid, characterized in that: include: Providing a micro powder material, wherein the micro powder material comprises abrasive particles and nano graphite powder; Providing a water-based composite carrier liquid, the water-based composite carrier liquid comprising an oxidant, a surfactant, a suspending agent, a defoaming agent, a dispersing agent, a pH regulator and water; wherein the defoaming agent is used to eliminate the foam generated by the polishing liquid during the polishing process and inhibit the generation of more foam, and the pH regulator is used to adjust the pH of the polishing liquid to 1-5; Mixing 2-40 parts of the micro powder material with 60-98 parts of a water-based composite carrier liquid in a mass ratio to obtain a polishing liquid; The defoaming agent includes one or more of propylene glycol, glycerol and mineral oil; The average particle size of the abrasive grains is 50nm-5μm, and the average particle size of the nano graphite powder is 20nm-500nm.

8. The preparation method according to claim 7, characterized in that: The mass ratio of each component in the water-based composite carrier liquid is: The water is 80-94 parts, the oxidant is 1-6 parts, the surfactant is 0.5-2 parts, the suspending agent is 0.1-0.5 parts, the defoaming agent is 0.1-0.3 parts, the dispersant is 0.5-4 parts, and the pH regulator is 0.05-0.3 parts.

9. The preparation method according to claim 7, characterized in that: The step of mixing 2-40 parts of the micro powder material with 60-98 parts of a water-based composite carrier liquid in a mass ratio to obtain a polishing liquid comprises: Mixing 1-6 parts of an oxidant, 0.5-2 parts of a surfactant, 0.1-0.5 parts of a suspending agent, 0.5-4 parts of a dispersant and 80-94 parts of water in a mass ratio to obtain a first water-based composite carrier liquid; The first water-based composite carrier liquid is mixed with 0.1-0.3 parts by weight of a defoamer to obtain a second water-based composite carrier liquid; Mixing the second water-based composite carrier liquid with the micro-powder material to obtain a first mixed liquid; The pH adjusting agent is added to the first mixed liquid to adjust the pH to 1-5 to obtain the polishing liquid.

10. The preparation method according to claim 7, characterized in that: The mass proportion of the abrasive particles in the micro powder is 20wt%-80wt%; The mass proportion of the nano graphite powder in the micro powder material is 20wt%-80wt%.